2015
DOI: 10.1007/s10856-015-5616-y
|View full text |Cite
|
Sign up to set email alerts
|

Reaction kinetics of dual setting α-tricalcium phosphate cements

Abstract: Addition of ductile polymers to calcium-deficient hydroxyapatite (CDHA)-forming bone cements based on α-tricalcium phosphate (α-TCP) is a promising approach to improve the mechanical performance of α-TCP cements and extend their application to load-bearing defects, which is else impeded by the brittleness of the hardened cement. One suitable polymer is poly-(2-hydroxyethylmethacrylate) (p-HEMA), which forms during cement setting by radical polymerisation of the monomer. In this study the hydration kinetics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 22 publications
2
87
0
Order By: Relevance
“…The addition of Gel to Col and the variation in crosslinking status can tailor many important material properties of resultant matrices. These include the dissolution resistance in different biological environments, the swelling characteristics and the mechanical strength [15, 25]. In conjunction with this data, the main objective of this research is to evaluate cell interaction with Col and Gel-based biomaterials with a particular focus on the chemical identity and availability of receptor recognition ligands for cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of Gel to Col and the variation in crosslinking status can tailor many important material properties of resultant matrices. These include the dissolution resistance in different biological environments, the swelling characteristics and the mechanical strength [15, 25]. In conjunction with this data, the main objective of this research is to evaluate cell interaction with Col and Gel-based biomaterials with a particular focus on the chemical identity and availability of receptor recognition ligands for cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we used UV irradiation and carbodiimide chemistry, based on the reaction with EDC (1-ethyl-3-(3-dimethylaminopropyl-carbodiimide hydrochloride) in the presence of NHS (N-hydroxy-succinimide), to tailor the physical characteristics of scaffolds [15, 25]. EDC crosslinking is a very effective method to increase the mechanical stability and the dissolution resistance of collagenous materials [2831].…”
Section: Introductionmentioning
confidence: 99%
“…The results from TGA analysis indicated that the addition of PLLA in PEEK decreased the thermal stability of scaffolds, as the starting decomposition temperature shifted to lower temperatures. In DSC curves, the endothermic peak at about 334 °C was attributed to the melting temperature of PEEK 27. Two endothermic peaks located at about 174 and 355 °C were attributed to the melting temperature and decomposition temperature of PLLA,28 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Tissue adhesives are attractive biomaterials to be used for treating meniscus tears [4]. They are already employed in clinical practice for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…Isocyanate-terminated polymers are of particular interest, since they have easily tuneable mechanical properties, they attach to the tissue via formation of strong covalent bonds and degrade to non-toxic products [4]. However, a drawback of this class of materials is the relatively long curing time: it can take up to several hours before the adhesive reaches maximum bonding strength.…”
Section: Introductionmentioning
confidence: 99%